Cardiac implantable electronic devices in patients with persistent left superior vena cava—A single center experience. (8th April 2020) - Ghazzal, Bahjat; Sabayon, Dean; Kiani, Soroosh; Leon, Angel R.; Delurgio, David; Patel, Anshul M.; Lloyd, Michael S.; Westerman, Stacy; Shah, Anand; Merchant, Faisal M.; El‐Chami, Mikhael F.
Abstract: Background: There are limited data on cardiac implantable electronic device implantation (CIED) in patients with persistent left superior vena cava (PLSVC). Objective: To describe the outcomes of implanting CIEDs with a focus on cardiac resynchronization therapy (CRT) in patients with PLSVC. Methods: We identified all patients with a PLSVC that underwent CIED implantation from December 2008 until February 2019 at our institution by querying the electronic medical record (n = 34). We then identified controls in a 3:1 fashion (n = 102) by matching on device type (CRT vs non‐CRT). Procedure success, complications, fluoroscopy and procedural time were recorded. Outcomes were compared using a two‐way analysis of variance test and conditional regression modeling for continuous and categorical variables, respectively. Results: A total of 34 patients with PLSVC underwent 38 procedures. Four patients underwent dual chamber system implantation followed by a subsequent upgrade to CRT. Thirteen patients underwent CRT implantation: one was implanted via the right subclavian while the rest were implanted via the PLSVC. Left ventricular ( P  = .06). Procedure and fluoroscopy times were significantly higher in the PLSVC as compared with the control group (97.7 vs 66.1 minute, P  < .001 and 18.1 minute vs 8.7 minutes, P  = .005, respectively). Conclusion: CIED implant in patients with PLSVC is feasible but technically more challenging and appears to be associated with higher risk of right ventricular lead dislodgment.